A new species of frog in the Litoria ewingii species group (Anura: Pelodryadidae) from south-eastern Australia - Mahony, Michael; Moses, Bede; Mahony, Stephen V.; Lemckert, Frank L.; Donnellan, Stephen (Zootaxa, 2020)
Population declines and range contractions among Australian frogs that commenced in the early 1980s continue in some species that were once widespread. The generality of this pattern has been difficult to discern, especially for those species that are encountered rarely because they have restricted periods of calling activity with poorly defined habitat preferences, and are not common. Several lines of evidence indicate that Litoria littlejohni is such a species. This frog was once known from mid-eastern New South Wales to eastern Victoria, and evidence from wildlife atlas databases and targeted searches indicate that it has declined in large portions of its former range, leaving several populations that are isolated, in some cases restricted in distribution, and of small size. We investigated the relationships among populations using mitochondrial ND4 nucleotide sequences and single nucleotide polymorphisms (SNPs) from the nuclear genome. We found that northern and southern populations form two highly divergent genetic groups whose distributions abut at the southern margin of the Sydney Basin Bioregion and these genetic groups also show divergence in morphology and male advertisement calls. Here we describe the populations to the south of the Sydney Basin Bioregion as a new species and provide information on its distribution and ecology. In light of the apparent isolation and small size of known populations of the new species and the consequent restriction of the range of L. littlejohni, we assessed the conservation status of both species.